Sobre democracia e direito à cidade na política urbana de Fortaleza: aportes teóricos e desafios práticos - Carvalho, Harley Sousa de (2017)
The right to the city is proposed as a new vision for the city where iniquities and violations of human dignity can be overcome, making the whole population benefit from the development of the city, while democratic management, through the inclusion in the decision-making process of the multiple interests existing in the city space, aims to promote this transformation and to realize the social function of the city and the well-being of its inhabitants. The justification of this research is based on the contrast between the mentioned normative expectation and the social reality of Fortaleza. The starting question of this work is: did the ideal of the right to the city and the conception of participatory democracy inherent in it produced an effective reorientation of the urban policy of Fortaleza? The general objective of the work is to investigate the theoretical foundations and practical challenges related to the problem. It follows the qualitative method with the use of bibliographical, statutory, documentary and non-participatory observation research. After presenting the social context of Fortaleza, it seeks to study the right to the city in its broad significance, in order to understand its theoretical genesis, followed by appropriation by the social moviment and, finally, its reception by the Brazilian legal system. Next, a diagnosis is made about the existing legislation and institutional practices that guide and structure the means of citizen participation within the scope of Fortaleza's urban policy, with emphasis on the 2009 Participatory Master Plan and the participation system proposed therein. In the last chapter, the purpose will be to evaluate which factors create obstacles for the democratic realization of the right to the city in Fortaleza, as well as to understand why the municipal public administration offers little openness for citizen participation, besides identifying reasons for The market is still the main agent external to the public administration to influence political-administrative decisions in terms of urban policy. Finally, it is sought to evaluate which factors contribute to a lower participation and a low power of influence of the civil society in what refers to the direction of the public action to attend the most basic and urgent needs of the city.